The reliability of evaluating conversations between people with traumatic brain injury and their communication partners via videoconferencing. Issue 6 (2nd July 2020) - Rietdijk, Rachael; Power, Emma; Brunner, Melissa; Togher, Leanne
ABSTRACT: There is growing interest in using telehealth to work with people with traumatic brain injury (TBI). This study investigated whether established rating scales for evaluating conversations of people with TBI are reliable for use over videoconferencing. Nineteen participants with TBI and their communication partners completed two conversation samples during both in-person (IP) and videoconferencing-based (VC) assessment, with randomised order of assessment. Independent clinicians evaluated the conversations using the Adapted Measure of Participation in Conversation (MPC), the Adapted Measure of Support in Conversation (MSC) and the Global Impression scales. Comparisons between IP and VC ratings identified no significant differences on the MPC, MSC, and four out of five of the Global Impression scales. There was a significant difference between IP and VC recordings for "Task Completion" ( p = .047), with participants performing significantly better in VC ratings. Inter-rater reliability was fair to excellent for the MPC and Global Impression scales for both IP and VC recordings. For the MSC scale, inter-rater reliability was poor to excellent. This study confirms the potential for using videoconferencing for evaluating conversations of people with TBI. Further development of training and rating procedures for these scales could facilitate more frequent and reliable use of these measures.